Design and Build of Supply Chain Management System Applications at PT. Gmindo Tape Industri - Sharyanto; Rio Budi Firmansyah; Bernadus Gunawan Sudarsono (Journal of Engineering, Technology and Computing (JETCom), 2022)
PT. GMINDO TAPE INDUSTRI a company that provides self adhesive tape manufacturer which is commonly called duct tape or adhesive tape for all kinds packing needs, from clear and brown OPP Tape, self adhesive tape, to OPP Printing. And we also have other types of OPP Tape such as Masking Tape, Double Side Tissue Tape, Double Side Foam Tape, and also Cloth Tape. Supply chain management at PT. Gmindo Tape Industry has been going well enough to process the product to hand consumers, but in data management there are still many shortcomings so that in reporting sometimes there is data that is not appropriate and human errors often occur in the process data management. Supply chain management must run well for smooth flow the goods went well as well as in data management. From the existing problems, a supply information system was designed and built chain management that is expected to handle these problems. In define requirements and analyze system development by collecting method data by means of observation, interviews and literature review from various sources information. For the method of analysis and design using Unfield Modeling Languages ​​(UML).